Building Multi-Source Supply Chain Resilience in Cloud Infrastructure: A Framework for Component, Manufacturing, and Geographic Risk Management - Natasha Mohan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the critical aspects of building resilient supply chain frameworks for cloud infrastructure technologies, focusing on component-level strategies, manufacturing integration, and geographic risk management. The article addresses the increasing complexities in supply chain management driven by the rapid evolution of cloud technologies and global market dynamics. Through analysis of multi-sourcing strategies, PCBA manufacturing considerations, and regional risk assessments, the article provides comprehensive insights into creating robust supply chain networks. The investigation encompasses various aspects including buffer inventory optimization, quality control systems, and sustainable practices in cloud infrastructure deployment. The article demonstrates how organizations can effectively manage supply chain vulnerabilities through advanced analytics, machine learning applications, and strategic geographic diversification. By examining real-world implementations and industry practices, this article offers valuable insights into the development of resilient supply chain frameworks that can adapt to market changes while maintaining operational efficiency in the cloud technology sector.
Keywords: Cloud Infrastructure Supply Chain; Multi-Source Manufacturing; Supply Chain Resilience; Geographic Risk Management; Sustainable Supply Chain Operations